A vigilância em saúde do trabalhador no Sistema Único de Saúde: uma análise a partir da atuação dos Centros de Referência na Paraíba - Xavier, Ana Paula Barbosa (2015)
This Master's Thesis is entitled "Surveillence of the Workers Health in the Health System: An Analysis from the performance of the Reference Centers in Paraiba" from the multiple movements that covered the construction of surveillance in workers' health within the Unified Health System (SUS). This research finds on the study of professional practice of surveillance technicians in Occupational Health (Visat) of the Worker's Health Reference Centers in the state of Paraiba (CEREST) which currently represent three macro-regional. In this sense, we present the workers' health scenario in Brazil related to the characteristics of surveillance model of the Workers Health and its Inclusion in the public health system as well as the mechanisms that led to the construction of CEREST, as well as the way that Service organizes the actions of Visat. To elaborate this scenario, we sought to articulate the theoretical contributions from the literature that discuss the categories of analysis that underlie the study of the object of research, and the discussions around the data from the social applied research together with technicians who Visat operate in the macro-regional CEREST in the state of Paraiba, supported in theoretical and critical framework of Marxist nature. During the: empirical research conducted in 2014, a representative sample accounted for 35% of the universe consists of 48 (forty-eight) technicians who work in three (3) macro-regional, whit houses the Regional Reference Centres, for Occupational Health in the state of Paraiba: Joao Pessoa, Campina Grande and Patos. Thus, the sample consisted of seventeen (17) technicians who work in the field of Health Surveillance of the worker CEREST. It is noteworthy that for the development of this research were respected all ethical principles that are embodied in the new Resolution no. 466 of December 12, 2012 of the National Health Council (CNS) approving the regulatory guidelines anh standards for research involving human subjects. In terms of methodology, quantitative and qualitative procedures, so that the data collection phase we used a structured interview and observation were used, and data interpretation phase we used descriptive statistics reading with the use of graphics and tables of contents and analysis by thematic categorization. Discussions of the results conclusively show that CEREST model as it has been outlined is a limitation to the construction of a model of health care workers, as provided for in SUS. Thus, show primary: move the municipalizatiin process, investing in inter-agency coordination, the reorganization of primary care and strengthening of social control over system management. From this study, it considered the need for radicalization of the health decentralization process of workers in the NHS and that Visat actions should seek further deepening of inter-institutional relations regarding the área.